MODEL PEMBELAJARAN PROBLEM POSING TIPE PRE SOLUTION POSING TERHADAP HASIL BELAJAR JURNAL UMUM SISWA - Delila Puspita Sari, Herdi, Rijal (JURNAL ILMU PENDIDIKAN, 2024)
The purpose of this research is to determine the effect of using the Problem Posing Learning Model, Pre SolutionPosing Type, on General Journal Learning Outcomes. This research uses a quantitative type of research. The population in this study were all class XI IPS students at SMA NEGERI 1 BADAR. The sample for this research was Xl IPS 2, totaling 30 students. This research instrument uses test questions which are used as data collection to see the results of students' general journal learning using the Problem Posing learning model, Pre Solution Posing Type. The research results showed that the tcount value was 3.1, while the ttable value at the significant level was 1.70. Therefore tcount > ttable or 3.1 > 1.701. Thus, the observation hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Conclusion: There is an influence of the learning model on general journal learning outcomes